Juridical Analysis of Notary Responsibilities Relating to Deed of Sale and Purchase Binding Agreement (PPJB) that Causes Disputes - Fariz Hadyanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to analyze and find out: 1). The Notary's responsibility in making the sale and purchase binding agreement (PPJB) that he made. 2). The solution to the making of the sale and purchase binding agreement (PPJB) in the event of a dispute.The approach method in this research isnormative juridical. The data used are primary and secondary data obtained through interviews and literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1). The Notary's responsibility in making the sale and purchase binding agreement (PPJB) that he made is if the sale and purchase agreement on land signed and made by a Notary made an error, it is not in accordance with the procedure for making it, then the Notary has legal responsibility to whom and to whom. who the deed of sale and purchase agreement is made, and if the Notary is proven to have made a mistake, whether intentional or unintentional, then the legal consequences that arise can be subject to sanctions according to the level of error or error in the binding deed of sale and purchase made by a Notary may be subject to sanctions including administrative sanctions 2). The solution to making a deed of sale and purchase binding agreement (PPJB) in the event of a dispute is through deliberation or through the courts. The aggrieved party can sue the party who caused the loss in court or by canceling the agreement that has been made by the parties. Dispute resolution using non-litigation or Alternative Dispute Resolution (ADR) is actually a family dispute resolution model compared to dispute resolution through judicial institutions which tend to be confrontational, taking into account wins and losses and ignores social elements in society. While the settlement through the judiciary is carried out if the deliberation efforts are not reached, then the settlement must be through the courts.